2016
DOI: 10.1007/s12593-010-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Ewings Sarcoma of the Hand–A Case Report

Abstract: Ewings sarcoma of the hand is relatively rare. Ewings sarcoma can present with minimal pain and swelling of the affected digit. The Erythrocyte sedimentation rate and C-reactive protein may be high. Radiologically, Ewings sarcoma can present with a plethora of features from permeative bone destruction to expansile lesions with or without periosteal reaction. Because of these features, this can be confused with Tuberculosis especially in a country like ours where Tuberculosis is endemic. This leads to starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Very few cases of malignant bone lesions of the hand are mentioned in the literature, and our study found only one case of EWS. EWS of the hand is relatively rare and presents with pain, swelling, a mass, or with clinical features of infection with fever and elevated inflammatory markers (22). These signs could be confused with a case of tuberculous tenosynovitis in regions where tuberculosis is endemic (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few cases of malignant bone lesions of the hand are mentioned in the literature, and our study found only one case of EWS. EWS of the hand is relatively rare and presents with pain, swelling, a mass, or with clinical features of infection with fever and elevated inflammatory markers (22). These signs could be confused with a case of tuberculous tenosynovitis in regions where tuberculosis is endemic (22).…”
Section: Discussionmentioning
confidence: 99%
“…EWS of the hand is relatively rare and presents with pain, swelling, a mass, or with clinical features of infection with fever and elevated inflammatory markers (22). These signs could be confused with a case of tuberculous tenosynovitis in regions where tuberculosis is endemic (22). Proper biopsy-guided management is of the utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…The most common locations in the hand are the metacarpal and proximal phalanxes. [ 3 ] The thumb (28%) and the middle finger (28%) are most commonly affected. [ 1 ] Men (69%) are affected more than the women, with the average age of occurrence being 18.5 years (5 months–51 years).…”
Section: Discussionmentioning
confidence: 99%
“…This may be confused with tuberculous dactylitis. [ 3 ] Radiologically, it may be seen as bone destruction and expansile lesion. On X-ray, it may be confused with osteomyelitis due to bone destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation